A customizable cryptographic service provider for an embedded cryptohardware system [electronic resource] - 178771 Illiasaak Ahmad (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2007